Cultural encounters in Songdogs - Garcia, Maura Xavier (Revista de Letras, 2007)
In this study we intend to show how the narratives of displacement, in the novel Songdogs, by Colum McCann, bring about distinct cultural elements in tension. As a consequence the narrator constitutes his hybrid identity. We start with an overview of the author and the novel, proceeding with a look at the main symbols that structure and the novel, proceeding with a look at the main symbols that structure the novel, examining the link between the historical and geographical narratives of displacement and the way cultural values are apprehended in their crossings, and finally reporting some ideas on how the narrator´s narratives of displacement resulted in a real "voyage of discovery" of his own self.